Implementación de seguridad en la capa de transporte del modelo TCP/IP en los servidores web y de aplicación de la Universidad Nacional de Loja. - Alvarado Sarango, Diego Javier (2017)
The present thesis project, is oriented to implement the SSL / TLS digital certificates in the web servers of la Universidad Nacional de Loja; For this purpose, the proposed methodology was used, divided into three phases: Analysis, design and implementation; Starting from the analysis, which detects the threats that affect the public institutional web portals, using as a tool the Kali Linux v2.0 operating system, which detected multiple vulnerabilities such as: Man in the Middle (Man in the middle), Phishing, Password Decryption, Denial of Service (DoS); to achieve this objective, we worked on a public servant, facilitated by the Telecommunication and Information Unit (TIU), to carry out the respective tests. At the design stage, the appropriate Certification Authority (CA) is chosen in both free and paid environments; to achieve this phase a comparison is made based on a systematic review on the important characteristics that a digital certificate must meet to be safe and the requirements of the la Universidad Nacional de Loja. In the implementation phase, the digital certificates are added to the web servers of la Universidad Nacional de Loja, in order to cover up the vulnerabilities found; to achieve this goal a penetration test was carried out, verifying that most vulnerabilities classified as high risk have been corrected.